O paciente com diagnóstico psiquiátrico e a sua história de vida - Nunes, Ana Carolina Baldan (Universidade Federal de São Carlos, 2023)
In 2011, in the context of the Psychiatric Reform, the Psychosocial Care Network was established. One of the services that make up the Network is the Psychosocial Care Center II Mental Disorder, intended for adult patients with mental disorders. The term “disorder” indicates the existence of a set of symptoms associated with suffering. Mental disorders are diagnosed using different systems. A psychiatric diagnosis is a tool that makes it possible to classify illnesses by means of symptoms. One of the systems used is the 10th revision of the International Classification of Diseases - ICD-10, which is officially adopted by health services in Brazil. Diagnoses are constructs aimed at understanding the world and not concrete and real objects, and their limits and value are widely discussed. There are, in general, two different positions on the subject. One of the positions argues that psychiatric diagnosis only labels unclassifiable people to legitimize medical power. The other position understands it as necessary for a proper understanding of the patient and to guide the therapeutic strategy. Different people with private lives relate in very own ways with their diagnoses, so the objective of the research is to understand how the psychiatric diagnosis relates to the individual's life history. The focus of the research is qualitative and the method used was the Life History. Six CAPS II users in São Carlos, with diagnoses provided for in the ICD-10, were interviewed, in addition to a service psychologist. Users' medical records were also analyzed. The interviewees presented multiple and diverse explanations for what makes them suffer, for their diagnoses and treatments, even those who are diagnosed with the same disorder, and these processes are intertwined with the life history of each one. It is already recognized that these processes are multifactorial. That said, life history is not a context or background that can cause, aggravate or alleviate an illness, but it is central, including in any form of care directed at the patient. The research, by giving voice to members of a historically marginalized and still very discriminated group, managed to investigate, from the Life History method, how the individual means his life history and his diagnosis and how they are intertwined.
The patient with a psychiatric diagnosis and his life history
Keywords: Diagnóstico psiquiátrico; CAPS; Paciente; História de vida; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA